"There's no way I'm gonna meet their expectations": - Millie Takazawa Chen (The Journal for Undergraduate Ethnography, 2023)
The persistent nature of patriarchal gender norms in Japan is well-known globally despite the nation’s commitment to achieving the UN’s Sustainable Development Goals, one of which includes gender equality. This paper seeks to introduce and explore the personal narratives of Japanese expatriate women and youth diaspora in the United States to understand how they perceive gender roles in Japanese society and culture. Over the course of two months in 2021, bilingual open-ended interviews were conducted with ethnic Japanese expatriates and diaspora residing primarily in the Mid-Atlantic United States. Utilizing attitude development theories and existing research on cultural identity, this study provides a new look at the intersections between gender roles, migration, and what it means to accept—or reject—identity. New avenues of research are recommended to further discussions of gender norms, culture, and community by including the lived experiences of historically underrepresented populations.